Free Control II. - Free Control; Iivanainen, Johanna, 1976-; Iivanainen, Mikko, 1975-; Kaakkuriniemi, Mikko; Lindgren, Lasse, 1977- ([Kustannuspaikka tuntematon] : MPI Records, 2001)
10 kappaletta.
Free Control (yhtye): Iivanainen, Johanna (lauluääni). Iivanainen, Mikko (kitara). Lindgren, Lasse (bassokitara). Kaakkuriniemi, Mikko (rummut).
Keywords: jazz; fuusiomusiikki